Cho biểu thức P bằng <2x-1/x+3 -x/3-x -3-10x/x ² -9> : x+2/x-3 a, tìm điều kiện xác định của P và rút gọn P b ,tìm các giá trị nguyên của x để P có

Question

Cho biểu thức
P bằng <2x-1/x+3 -x/3-x -3-10x/x ² -9> : x+2/x-3
a, tìm điều kiện xác định của P và rút gọn P
b ,tìm các giá trị nguyên của x để P có giá trị nguyên

in progress 0
Valerie 3 ngày 2021-12-06T18:51:27+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-12-06T18:53:14+00:00

    P=(2x−1x+3−x3−x−3−10xx2−9):x+2x−3a)ĐKXĐ:x2−9≠0⇔x≠±3P=[(2x−1)(x−3)(x+3)(x−3)+x(x+3)(x+3)(x−3)−3−10x(x+3)(x−3)]:x+2x−3→P=2×2−7x+3+x2+3x−3+10x(x+3)(x−3)⋅x−3x+2→P=3×2+6xx+3⋅1x+2→P=3x(x+2)x+3⋅1x+2→P=3xx+3b)P=3xx+3=3x+3−3x+3=3(x+1)−3x+3=3−3x+3P∈Z⇔3x+3∈Z⇔x+3∈Ư(3)={−3;−1;1;3}⇔x={−4;−2;0;2}

     

     

    0
    2021-12-06T18:53:26+00:00

    $\begin{array}{l}\quad P = \left(\dfrac{2x-1}{x+3}-\dfrac{x}{3-x} – \dfrac{3-10x}{x^2 – 9}\right):\dfrac{x+2}{x-3}\\ a)\quad ĐKXĐ: x^2 – 9 \ne 0\Leftrightarrow x \ne \pm 3\\ \quad P = \left[\dfrac{(2x-1)(x-3)}{(x+3)(x-3)}+\dfrac{x(x+3)}{(x+3)(x-3)} – \dfrac{3-10x}{(x+3)(x-3)}\right]:\dfrac{x+2}{x-3}\\ \to P = \dfrac{2x^2-7x + 3+x^2 +3x- 3 + 10x}{(x+3)(x-3)}\cdot\dfrac{x-3}{x+2}\\ \to P = \dfrac{3x^2+6x}{x+3}\cdot\dfrac{1}{x+2}\\ \to P = \dfrac{3x(x+2)}{x+3}\cdot\dfrac{1}{x+2}\\ \to P = \dfrac{3x}{x+3}\\\\ b)\quad P = \dfrac{3x}{x+3} = \dfrac{3x+3 -3}{x+3} = \dfrac{3(x+1) – 3}{x+3} = 3 – \dfrac{3}{x+3}\\ P\in\Bbb Z \Leftrightarrow \dfrac{3}{x+3} \in\Bbb Z\\ \Leftrightarrow x+3 \in Ư(3)=\{-3;-1;1;3\}\\ \Leftrightarrow x = \{-4;-2;0;2\} \end{array}$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )